Une rhétorique pour faire revivre un monde oublié : de lʼekphrasis à lʼhypotypose dans La Sagouine dʼAntonine Maillet - Zacharow, Sebastian (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2018)
The play of Antonine Maillet La Sagouine was written over 200 years after the brutal expulsion of the Akadians from Canada. The heroine of the monodrama is an Akadian called Sagouine, a laundress and a wife of a fisherman. She never learnt to read or write. She can however narrate and does so with a lot of charm. The play is full of descriptions of people and situations, which strongly act on the imagination of the receiver contributing to the rhetorical function of placere. Stylistic treatments used by the heroine to revive descriptions arise from the cultural context (the heroine often emphasizes her lack of any education) and the particular viewer, and the descriptions themselves are an example of the creation of hypotyposis by modest means. Thus the article stresses that hypotyposis is not a figure reserved only for “great” classical works, but is also used in contemporary literature, the theater, or, as in the case of La Sagouine, in radio broadcasting.